Integrated phenotypic and genomics analysis to elucidate differences in stress resistance and virulence of Listeria monocytogenes strains. Issue Volume 1(2019)Issue A (8th March 2019) - Stratakos, Alexandros; Linton, Mark; Ward, Patrick; Ijaz, Umer; Scates, Pam; McBride, Jane; Gundogdu, Ozan; Corcionivoschi, Nicolae
Abstract : Listeriosis is an important food-borne disease responsible for high rates of morbidity and mortality. L. monocytogenes has been the cause of several food-borne outbreaks and product recalls throughout the world. It can adapt and survive in a wide range of stress conditions which makes it difficult for food producers to eradicate. The goal of this study was to use phenotypic assays and whole genome sequencing to elucidate possible links between food related stress resistance and virulence phenotypes in L. monocytogenes strains originating from different sources. Four L. monocytogenes isolates from sweetcorn and one isolate from a food processing environment (control) were sequenced and evaluated for the ability to survive in acid (pH 3.5, 15 min), in the presence of a commercial antimicrobial mixture (2 % v/v, 90 min), heat (60 °C, 5 min) and hydrogen peroxide (420 mM, 15 min). Results showed that the strains had different resistance levels to the above stressors with the environmental strain being more susceptible to heat and the commercial antimicrobial. Also, results showed that the four sweetcorn isolates were more virulent than the environmental isolate as they had significantly higher attachment and invasion capacity onto HCT-8 cells (P Pan-genome analysis revealed that the four isolates fall within a class associated with recent outbreak strains. Single Nucleotide Polymorphisms (SNPs) analysis was performed on the five genome sequences and subsequent cluster analyses on the resulting whole genome SNP matrix revealed differences between the strains.